The Reality of Interdisciplinary Postgraduate Programs at Tabuk University, Their Challenges, and Requirements for Activating them from the Perspective of Academic Leaders - Al-Onizy, Marzooqah Abdullah; Al-Sharif, Abdullah Abdulaziz (Journal of Educational and Psychological Sciences, 2025)
The study aimed to diagnose the reality of interdisciplinary postgraduate programs in their dimensions (administrative, organizational, and financial) at Tabuk University from the perspective of academic leaders, and to reveal the challenges they face and the requirements for their activation. The descriptive survey approach was used, and the questionnaire was used as a tool. The study relied on the method of a comprehensive survey of academic leaders at the university, numbering (144) academic leaders. (20) academic leaders who participated in the survey sample were excluded, so their number became (124) academic leaders, and (87) of them responded with a response rate of (70%). The results revealed that the requirements for activating interdisciplinary programs came first with an overall average of (4.17 out of 5), followed by the challenges they face with an average of (3.58) and both with a (large) rating, and third, their reality with an average of (3.32) and a (medium) rating. Based on the results, the study recommended enhancing coordination between the faculties at Tabuk University and the labor market, establishing a joint unit for interdisciplinary graduate programs at the university, ensuring continuous digital marketing, diversifying sources of income, and leveraging the experience of the Master's Program in Executive Forensic Accounting. The study recommended ensuring appropriate tuition fees, ensuring careful selection of interdisciplinary programs, and enhancing and investing in the technical and scientific infrastructure. It also presented research proposals related to marketing strategies for Postgraduate programs at universities, the role of activating interdisciplinary Postgraduate programs in enhancing the academic and research reputation of universities, and student and faculty attitudes toward interdisciplinary programs.
Keywords: Interdisciplinary Postgraduate programs; interdisciplinary studies; Tabuk University; academic leadership opinions